A Prospective 5-Year Re-examination of Alcohol Response in Heavy Drinkers Progressing in Alcohol Use Disorder - King, Andrea C.; Hasin, Deborah; O’Connor, Sean J.; McNamara, Patrick J.; Cao, Dingcai (Biological psychiatry (1969), 2016)
The main neurobiological theories of the development of addiction, including tolerance, sensitization, incentive-sensitization, and allostasis, have not been tested in longitudinal human alcohol response research. To address this issue, we conducted the first controlled prospective investigation of subjective and neuroendocrine responses to alcohol measured over a 5-year interval in at-risk young adult heavy drinkers (HD) and light drinker control subjects. Participants were 156 individuals, 86 heavy drinkers and 70 light drinkers, undergoing an initial oral alcohol challenge testing (.8 g/kg alcohol vs. placebo) and an identical re-examination testing 5 to 6 years later. Alcohol use disorder (AUD) symptoms and drinking behaviors were assessed in the interim follow-up period. At re-examination, HD continued to exhibit higher sensitivity on alcohol’s stimulating and rewarding effects with lower sensitivity to sedative effects and cortisol reactivity, relative to light drinkers. In HD with high AUD symptom trajectories over follow-up, heightened alcohol stimulation and reward persisted at re-examination. HD with low AUD symptoms showed reduced alcohol stimulation over time and lower reward throughout compared with the HD with high and intermediate AUD symptoms. Results support the early stage phase of the allostasis model, with persistently heightened reward sensitivity and stimulation in heavy drinkers exhibiting AUD progression in early mid-adulthood. While there are multiple pathways to development of a disorder as complex as AUD, maintenance of alcohol stimulatory and rewarding effects may play an important role in the continuation and progression of alcohol addiction.